1986
DOI: 10.1021/bi00359a045
|View full text |Cite
|
Sign up to set email alerts
|

Topography of oligomycin sensitivity conferring protein in the mitochondrial adenosine triphosphatase-ATP synthase

Abstract: The topographical organization of oligomycin sensitivity conferring protein (OSCP) in the mitochondrial adenosinetriphosphatase (ATPase)-ATP synthase complex has been studied. The accessibility of OSCP to monoclonal antibodies has been qualitatively visualized by using the protein A-gold electron microscopy immunocytochemistry or quantitatively estimated by immunotitration of OSCP in depolymerized or intact membranes. Besides, OSCP cannot be labeled by 3-(trifluoromethyl)-3-(m-[125I]iodophenyl)diazirine ([125I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Furthermore, there is experimental evidence that a 24-kDa component of an Fo preparation from beef heart is in fact identical to subunit 6 (91). In addition, the 24-kDa protein seems to be adjacent to OSCP as has been inferred from cross-linking studies (9,205). The precise role of this subunit is still unknown; however, as discussed for E. coli, it might have a structural function.…”
Section: Subunit Compositionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, there is experimental evidence that a 24-kDa component of an Fo preparation from beef heart is in fact identical to subunit 6 (91). In addition, the 24-kDa protein seems to be adjacent to OSCP as has been inferred from cross-linking studies (9,205). The precise role of this subunit is still unknown; however, as discussed for E. coli, it might have a structural function.…”
Section: Subunit Compositionmentioning
confidence: 77%
“…Both proteins are required for the binding of F1 to the membrane sector and for rendering the F1 complex sensitive to inhibition by oligomycin and DCCD (157,210). Cross-linking experiments with the F1Fo complex from pig heart mitochondria revealed that OSCP is in close proximity to a and ,B of F1 (9). Surprisingly, Sandri et al (161) recently provided evidence for an Fl-binding site on Fo in the absence of F6 and OSCP; however, the ATPase activity of this complex was insensitive towards DCCD.…”
Section: Subunit Compositionmentioning
confidence: 99%
“…Cross-linking of membrane bound IF, with N-(ethoxycarbonyl)-Zethoxy-l-2-dihydroquinoline (EEDQ) was performed as described previously for the study of nearest neighbours of oligomycin-sensitivity-conferring protein in the mitochondria1 membrane (Archinard et al, 1986). Cross-linking experiments with 0.5 mM bis(2-[succinimidooxycarbonyloxy]ethyl)sulfone) (BSOCOES) and ETP (0.9 mg/ml in 25 mM sodium phosphate, pH 7.5) were performed for 15 min at 0°C in the presence of 0.5 mM BSOCOES.…”
Section: Cross-linkingmentioning
confidence: 99%
“…Cross-linking of membrane bound IF, with N-(ethoxycarbonyl)-Zethoxy-l-2-dihydroquinoline (EEDQ) was performed as described previously for the study of nearest neighbours of oligomycin-sensitivity-conferring protein in the mitochondria1 membrane (Archinard et al, 1986). Experimental conditions were as described in Materials and Methods.…”
Section: Cross-linkingmentioning
confidence: 99%
“…Based on the data presented, we suggest that (i) the K181-L190 region at the C-terminal end of OSCP encompasses an R-helix or part of an R-helix, and (ii) interactions between the C-terminal end of OSCP and subunit(s) of F o in the F 1 -F o enzyme do not specifically require acidic or basic residues, or residues with uncharged side chain, but do involve an R-helix. F 1 F o , as well as cross-linking of intact F 1 F o enzyme using cross-linking reagents of different chemical reactivities and effective distances (0-12 Å) (Archinard et al, 1986;Joshi & Burrows, 1990;Belogrudov et al, 1995). Beckers et al (1992) showed formation of a cross-link between a basic amino acid residue of CF 1 δ and an acidic residue at the C-terminal end of CF o b.…”
Section: Discussionmentioning
confidence: 99%